PENGARUH PROFITABILITAS DAN FINANCIAL DECISION PADA NILAI PERUSAHAAN STUDI PADA PERUSAHAAN JASA, DAGANGAN, DAN INVESTASI YANG TERDAFTAR DI BEI PERIODE 2014-2016 - Ni Luh Mita Miati; I Putu Gede Wisnu Permana Kawisana; Ni Luh Putu Ratna Wahyu (Jurnal Riset Akuntansi, 2017)
This study aims to determine the influence Profitability and Financial Decision on Firm Values. This research is conducted on service companies, trade, and investment on the Indonesia Stock Exchange, with total population of 36 companies, as well as using non-probability sampling method, using purposive sampling technique in order to obtain the 26 companies for sample. PBV (Price Book Value) ratio is used to measure the firm value Company, while the indicators of the ROE (Return on Equity) for measuring profitability, EPS (earning per share) to measure investation decision, and PER (Price Earning Ratio) to measure funding decision. The regression model has passed the test classic assumptions. The analysis showed that the profutability and funding decision has no significant positive effect, while investation decision has a significant positive effect on the value of the company. 10 companies for the sample